2013
DOI: 10.1111/bjhp.12055
|View full text |Cite
|
Sign up to set email alerts
|

Not intending but somewhat willing: The influence of visual primes on risky sex decisions

Abstract: Objectives This article investigates a potential mechanism underlying the “sexually conservative puzzle” (the scenario where people reporting little to no casual sex intentions nevertheless go on to engage in casual sex). Methods In two experiments, we tested whether people reporting no behavioral intentions (BI) for casual sex were nevertheless more responsive to risk-conducive cues, when compared to those with some BI. Responsiveness to cues was assessed in terms of increases in behavioral willingness (BW)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Although there are studies using priming that demonstrate that the mere exposure to risk-inductive cues can increase associated risk cognitions and behavior (Bartholow & Heinz, 2006; Harris, Brownell, & Bargh, 2009; Roberts, Gibbons, Kingsbury, & Gerrard, 2014), little is known about actual real-life daily variations in risk-conducive situations and how they impact risk cognitions. As such, the present study is an important first step in understanding how risk cognitions such as behavioral willingness are sensitive to daily changes in context.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are studies using priming that demonstrate that the mere exposure to risk-inductive cues can increase associated risk cognitions and behavior (Bartholow & Heinz, 2006; Harris, Brownell, & Bargh, 2009; Roberts, Gibbons, Kingsbury, & Gerrard, 2014), little is known about actual real-life daily variations in risk-conducive situations and how they impact risk cognitions. As such, the present study is an important first step in understanding how risk cognitions such as behavioral willingness are sensitive to daily changes in context.…”
Section: Discussionmentioning
confidence: 99%
“…For example, when dissatisfaction within a relationship is caused by sexual dissatisfaction within the relationship (Sprecher & Cate, 2004), women may be more susceptible to sexual media content than when dissatisfaction is caused by nonsexual factors. Moreover, a study by Roberts et al (2013) showed that the effect of showing erotic material to men on willingness to engage in casual sex was affected by behavioral intentions to engage in casual sex. Thus, differences in behavioral intentions, together with different reasons for women’s satisfaction with their relationship or being single, should be taken into account in future research.…”
Section: Methodsmentioning
confidence: 99%
“…According to some studies, people may be more willing to engage in these behaviors or act irrationally in the moment (due to arousal, when visually primed, or peer-pressured), but have lower explicit intentions to engage in these behaviors in the abstract. 65 Future research might examine willingness to engage in risky sexual behaviors, under a range of interpersonal and contextual conditions, in addition to assessing behavioral intentions. Furthermore, this study uses intentions as a proxy for actual behavior.…”
Section: Limitationsmentioning
confidence: 99%